Immune mechanisms in heart failure - Zhang, Yingying; Bauersachs, Johann; Langer, Harald F. (European journal of heart failure, 2017)
Elevated levels of circulating pro‐inflammatory biomarkers in patients with both ischaemic and non‐ischaemic heart failure (HF) correlate with disease severity and prognosis. Experimental studies have shown activation of immune response mechanisms in the heart to provoke cardiac adverse remodelling and cause left ventricular dysfunction. Consequently, most of the clinical trials targeting elements of the immune response in HF attempted to modulate the inflammatory response. Surprisingly, clinical studies targeting immune effectors were either neutral or even increased pre‐specified clinical endpoints, and some studies resulted in worsening of HF. This review discusses immune mediators involved in the pathogenesis and progression of HF and potential therapeutic applications targeting inflammation in HF. Besides more obvious settings featuring immune activation such as inflammatory or ischaemic cardiomyopathy, the relevance of immune activation in acute or chronic HF of other origins, including volume overload or valvular heart disease, is highlighted. Understanding how cell‐specific and molecular mechanisms of the immune response interfere with cardiac remodelling in HF may open new avenues to design biomarkers or druggable targets.